The Perception of High School Communities towards River Restoration Program - Atie Tri Juniati; Dwi Ariyani; Nuryani Tinumbia; Fadli Kurnia; Atri Prautama Dewi; Gatut Bayuaji; Hera Hera; Nono Carsono (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2021)
River restoration is an activity to restore the river's condition to its original state. River restoration is one of the SDGs targets, namely target 6.6, Aquatic Ecosystems.The target of 6.6 SDGs is to conserve and restore water-related ecosystems such as mountains, forests, wetland vegetation, rivers, reservoirs and lakes. These SDGs targets will be successful with the participation of the surrounding community. In order to pursue this target, the Civil Engineering Study Program, Pancasila University has organized a community service program related to river restoration activities, in the Cimanuk-Cisanggarung river area, Cirebon. Community service activities are carried out by providing counseling about the importance of river restoration programs to high school teachers and assessing school readiness to form a water quality monitoring school partnership. To assess the understanding of river restoration and the readiness to establish partnership, a questionnaire was given. Based on the questionnaire analysis, it can be concluded that most of the participants (76%) stated that the river restoration program was important, and would be ready to partner with other schools (24%). This shows that program respondents are ready to form partnerships to support river restoration programs.